Normal Weight Estonian Prepubertal Boys Show a More Cardiovascular-Risk-Associated Adipose Tissue Distribution than Austrian Counterparts. (14th January 2013) - Wallner-Liebmann, Sandra J.; Moeller, Reinhard; Horejsi, Renate; Jürimäe, Toivo; Jürimäe, Jaak; Mäestu, Jarek; Purge, Priit; Saar, Meeli; Tafeit, Erwin; Kaimbacher, Petra; Kruschitz, Renate; Weghuber, Daniel; et al.
Abstract : Objective . Risk phenotypes for cardiovascular disease (CVD) differ markedly between countries, like the reported high difference in CVD mortality in Austria and Estonia. Hitherto, the goal of this study was to find out risk profiles in body fat distribution yet present in childhood, paving the way for later clinical end points. Methods . he subcutaneous adipose tissue (SAT) distribution patterns in 553 Austrian (A) and Estonian (E) clinically healthy normal weight boys aged 11.1 (±0.8) years were analysed. We applied the patented optical device Lipometer which determines the individual subcutaneous adipose tissue topography (SAT-Top). Results . Total body fat did not differ significantly between E and A boys. A discriminant analysis using all Lipometer data, BMI, and the total body fat (TBF) yielded 84.6% of the boys correctly classified in Estonians and Austrians by 9 body sites. A factor analysis identified the SAT distribution of E as critically similar to male adult patients with coronary heart disease (CHD). Conclusions . We show in normal weight Estonian boys a highly significant decreased fat accumulation on the lower body site compared to age matched Austrian males. This SAT-Top phenotype may play an important role for the increased cardiovascular risk seen in the Estonian population.